State Defense Awareness Strengthening of East Java Veteran National Development University Student Through Online Learning in Supporting National Defense - Suprapto, Suprapto; Dwi Ari Purwanto; Tatar Bonar (Universitas Negeri Surabaya, 2021)
The purpose of this research is to conduct an analytical study on how the program strengthens student defense awareness through online learning, in view of planning, implementation, supporting resources and obstacles faced. This research was conducted at the East Java Veterans National Development University. Research uses qualitative methods with data collection techniques namely observation, interview, documentation and focus group discussion. The source of informants consists of the University Leader, Coordinator of State Defense Education Courses, Lecturers, Information Technology Technicians and Students. The results of this study are: Program planning is designed in accordance with the Vision and Mission of the University; Resource readiness is good enough to support the program; and the strengthening program can be implemented properly; Program barriers include learning time requirements, Lack of control Lecturers over students, slow networking and server storage limitations. The conclusion of this research is that the strengthening of student defense awareness can be carried out through online learning, in supporting the national defense. Keywords: National Defense Awareness, online learning, strengthening program .